The feasibility and safety of immediate breast reconstruction in the COVID-19 era. Issue 11 (November 2020) - Jallali, Navid; Hunter, Judith E.; Henry, Francis P.; Wood, Simon H.; Hogben, Katy; Almufti, Ragheed; Hadjiminas, Dimitri; Dunne, Jonathan; Thiruchelvam, Paul T.R.; Leff, Daniel R.
Summary: The coronavirus disease-2019 pandemic has had a significant impact on the delivery of surgical services, particularly reconstructive surgery. This article examines the current evidence to assess the feasibility of recommencing immediate breast reconstruction services during the pandemic and highlights considerations required to ensure patient safety.